The Influence of Good Corporate Governance on Company Value of Sharia-compliant Issuers in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange in 2022–2024 - Asyifa Zahra; Safaruddin; Yusri Hazmi (Britain International for Academic Research (BIAR) Publisher, 2026)
Company value is an important indicator that reflects a company's success in creating prosperity for shareholders and is also a primary consideration for investors in making investment decisions.Good Corporate Governance It is believed to be able to improve the quality of corporate governance through effective oversight mechanisms, although the results of previous research on the influence of each governance mechanism on company value still show inconsistencies. This study aims to analyze the influence Good Corporate Governance This study examines the effect of gender diversity, audit committees, independent commissioners, and institutional ownership on firm value in sharia-compliant issuers in the food and beverage sub sector listed on the Indonesia Stock Exchange in 2022–2024. The study employed a quantitative approach with secondary data obtained from the companies' annual reports. The sample was determined using a random sampling technique.purposive sampling, resulting in 26 companies with 78 observation units. Data analysis was performed using panel data regression through the views 13 application, with Random Effect Models the best estimation model. The results show that the audit committee, independent commissioners, and institutional ownership have a positive and significant effect on firm value, while gender diversity has no significant effect. Simultaneously, all mechanisms Good Corporate Governance has a significant impact on company value. This finding indicates that the effectiveness of implementing corporate governance mechanisms is a strategic factor in increasing company value and strengthening investor confidence in the company.